2023
DOI: 10.1039/d3en00124e
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical inactivation of enteric viruses MS2, T4, and Phi6 using doped laser-induced graphene electrodes and filters

Abstract: Pathogenic virus inactivation is crucial to eliminate the substantial risk they cause to human health and to ensure safe drinking water. Conventional water disinfection methods generate harmful disinfection by-products, and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 88 publications
(137 reference statements)
4
11
0
Order By: Relevance
“…Due to laser irradiation, the sheet surface turned into a highly porous forest-like structure (Figure a–c) due to the rapid release of gaseous products. , The fibrous structures for LIG, Fe-LIG, and SFe-LIG are also clearly visible in Figure d–i. Such forest-like porous and fibrous structures have also been reported in previous LIG fabrication studies. ,,, For elemental analysis, SEM-EDS of the LIG, Fe-LIG, and SFe-LIG sheets has also been done (Figures S4–S6). As shown in Figure S4, LIG sheets are composed of mainly carbon, oxygen, and sulfur.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Due to laser irradiation, the sheet surface turned into a highly porous forest-like structure (Figure a–c) due to the rapid release of gaseous products. , The fibrous structures for LIG, Fe-LIG, and SFe-LIG are also clearly visible in Figure d–i. Such forest-like porous and fibrous structures have also been reported in previous LIG fabrication studies. ,,, For elemental analysis, SEM-EDS of the LIG, Fe-LIG, and SFe-LIG sheets has also been done (Figures S4–S6). As shown in Figure S4, LIG sheets are composed of mainly carbon, oxygen, and sulfur.…”
Section: Resultssupporting
confidence: 75%
“…The SEM images of LIG (Figure a,d,g), Fe-LIG (Figure b,e,h), and SFe-LIG filters (Figure c,f,i) at various magnifications are shown in Figure . Similar to the sheets, the filter’s surface turned into a forest-like, highly porous, and fibrous structure, as discussed in previous LIG fabrication studies. ,,, …”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…[21][22][23][24][25] Detailed literature reviews on ECMs, LIG and their environmental application can be found elsewhere. 9,10,18,26,27 Advanced oxidation processes (AOPs) play a key role in pollutant degradation, chemical oxidation, and wastewater treatment due to the production of highly reactive radicals. 28 With the research and development of AOPs, sulfate radicalbased AOPs (SR-AOPs) have emerged as a sub-category.…”
Section: Introductionmentioning
confidence: 99%
“…21–25 Detailed literature reviews on ECMs, LIG and their environmental application can be found elsewhere. 9,10,18,26,27…”
Section: Introductionmentioning
confidence: 99%